Lifecycle of a technology company : step-by-step legal background and practical guide from start-up to sale - Miller, Edwin L., Jr., 1947- (Hoboken, N.J. : J. Wiley, 2008)
This book helps to create a solid foundation for those who are in the technology sector. It allows the entrepreneur to understand more deeply the legal milieu in which they operate and provides venture capitalists with a better understanding of the ration.
Start-up phase -- Financing the venture -- Intellectual property protection -- Private placements, initial public offerings, and public company regulation -- Acquisitions.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: High technology industries -- Law and legislation -- United States; High technology industries -- Finance -- Law and legislation -- United States; Intellectual property -- United States; Consolidation and merger of corporations -- United States; z; Entreprises -- Fusion; LAW -- Administrative Law & Regulatory Practice; Consolidation and merger of corporations; High technology industries -- Finance -- Law and legislation; High technology industries -- Law and legislation; Intellectual property; United States